Strategy Outdoor and Knowlledge Biodiversity Toward New Raradigm Environment Secondary Student Bandarlampung - Arwin Surbakti (IJEEM - Indonesian Journal of Environmental Education and Management, 2017)
This study aims to determine the effect of outdoor strategies and knowledge biodiversity toward new paradigm environmental (NEP). The method used in this study is an experiment with 2 x 2 factorial design. The study population was student senior high school Bandarlampung, numbered 64 student. Data analysis technique used is the Two-Way Analysis of Variance followed by Tukkey test. The findings of this study include: 1. There is the NEP of the student were taught with strategy outdoor in TNWK and strategy outdoor in around school. 2. The participants biodiversity who knowledge higher outdoor strategy in TNWK and strategy outdoor around school, who were no taught with the NEP. 3. The participants biodiversity knowledge lower with outdoor in strategy TNWK and strategy outdoor around school, who were taught for the NEP. 4. There is no positive interaction influence between outdoor in strategy TNWK and strategy outdoor around school. Based on these findings we can conclude that there is no extension strategies are most effective, depending on background knowledge biodiversitas of student.